Influence of Migration Flows and Remittance Patterns on Rural Development and Poverty Reduction Policies - Mohammad Sofyan; Rodhiyah; Musennif Zeynaddin Shabanov (Global Economics: International Journal of Economic, Social and Development Sciences, 2024)
Migration and remittances have long been recognized as critical components of rural development and poverty alleviation, particularly in developing countries. This study explores the impact of migration flows and remittance patterns on local economies, focusing on their role in poverty reduction, community resilience, and sustainable rural development. Migration, particularly rural-to-urban and international migration, brings significant financial flows in the form of remittances, which improve household welfare by supporting basic needs such as food, education, and healthcare. Moreover, these remittances often stimulate local investment, particularly in agriculture and small businesses, contributing to economic diversification in rural areas. However, the effectiveness of these financial transfers varies regionally, with some areas experiencing greater benefits than others due to differences in infrastructure, financial services, and migration policies. While remittances contribute to poverty reduction and socio-economic stability, they are often underutilized for long-term investments due to their primary use for consumption rather than productive projects. Government assistance programs, on the other hand, focus on structural poverty alleviation but often face challenges in terms of reach, effectiveness, and sustainability in rural areas. This study concludes with policy recommendations aimed at maximizing the impact of remittances, including reducing transaction costs, encouraging investment, and improving financial inclusion in rural communities. Additionally, it suggests further research into the role of migration policies in facilitating remittances and enhancing their developmental impact. The findings underscore the importance of integrating migration and remittance-focused strategies into national rural development plans to foster sustainable economic growth and reduce rural poverty.